Liability of the Public Administration: notes for a change proposal in the Peruvian Law of General Administrative Procedure - Villavicencio Escudero, Lucía Alexandra (2018)
In the first part, the paper analyzes the elements of the Liability of the Public Administration and the objectives that this legal form pursues. In a second section, it analyzes the Peruvian regulations in this field, finding flaws and gaps, suggesting changes so that the regulation achieves the purpose that the Liability of the Public Administration proposes. Through this change proposal, the author pretends that this legal form becomes truly enforceable in practice.